2013
DOI: 10.1111/eje.12058
|View full text |Cite
|
Sign up to set email alerts
|

Pairing as an instructional strategy to promote soft skills amongst clinical dental students

Abstract: Training dentists today is challenging as they are expected to provide a wide range of dental care. In the provision of good dental care, soft skills are equally important as clinical skills. Therefore in dental education the development of soft skills are of prime concern. This study sought to identify the development of soft skills when dental students are paired in their clinical training. In this perception study, four open-ended items were used to elicit students ' feedback on the appropriateness of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
(46 reference statements)
2
19
0
1
Order By: Relevance
“…Our findings revealed that the majority of students were not satisfied with their assistants' performance in the clinic. To overcome this issue, Abu Kassim and colleagues recommended that an assessment should be incorporated when assigning operator–student pairs in clinics to encourage positive behaviours of the assistants and improve the students' learning experience overall. It has been suggested that soft skills development is important to prevent the students from being stereotype in their clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that the majority of students were not satisfied with their assistants' performance in the clinic. To overcome this issue, Abu Kassim and colleagues recommended that an assessment should be incorporated when assigning operator–student pairs in clinics to encourage positive behaviours of the assistants and improve the students' learning experience overall. It has been suggested that soft skills development is important to prevent the students from being stereotype in their clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing has been considered as a strategy to promote soft skills amongst dental students . However, a recent published study described that although students recognised the value of working in a team, they also had considerable problems in their interactions . This has been supported by another observation that maintained that working together is a skill that has to be learned and should be a fundamental consideration in the dental curricula .…”
Section: Discussionmentioning
confidence: 99%
“…They are therefore used to being judged and observed by an equivalent treatment partner with similar levels of knowledge. Here, Kasim et al found that soft skills like communication and team work benefited from the pairwise collaboration of two students . A US‐American study showed that doctors are only partially capable of self‐reflection, at least with regard to the assessment of their learning needs.…”
Section: Discussionmentioning
confidence: 99%